Monkeypox: From A Neglected Tropical Disease to a Public Health Threat - Antunes, Francisco (2022)
Since the first case of human monkeypox was diagnosed in 1970, the disease remained endemic in several countries in West and Central Africa. In 1996, there was a sudden increase in cases in the Democratic Republic of Congo (DRC), and since 2017 an ongoing outbreak in Nigeria took place, probably related to the population growth, human invasion of MPXV animal habitat reservoirs, and the waning of the cross-protection offered from smallpox immunization, later ending in 1980. Since May 2022, an unprecedented outbreak of human monkeypox has rapidly spread around the world, outside endemic regions of Africa, through new modes of transmission, showing differences in clinical features compared with previous reports. The 2022 MPXV strain belongs to the clade of West Africa but diverges from the original strain, making the virus more transmissible. The authors review the main milestones in more than 50 years of history of human monkeypox, from a rare viral zoonotic infection to a public health emergency.